Selection of Supply Chain Performance Measurement Frameworks in Electrical Supply Chains - Galankashi, Masoud Rahiminezhad; Memari, Ashkan; Anjomshoae, Ali; Ma'aram, Azanizawati; Helmi, Syed Ahmad (International Journal of Industrial Engineering and Management, 2014)
Performancemeasurement plays an important role in today’s competitive market due to its direct effect on supply chain's profitability. Many approaches have been applied for evaluating performance of firms, including financial, operational and balanced frameworks. Companies peruse to find the best fit performance measurement framework due to a variety of existing approaches. The main significance ofperformance framework selection is its important role in strategic decisions where many factors related to the companies’ performance may be neglected. Due to the nature of electrical companies such as high uncertainty in demand, short life cycle of products and competitive market, they have to frequently assess their performance. A fit framework should be determined based on the characteristics of this competitive market. In this study, a multi criteria decision making (MCDM) approachisused to find a proper framework for performance evaluation in electrical companies. Analytical hierarchical process (AHP) has been applied to select the best performance measurement framework based on supply chain macro processes. Finally, performance metrics for the selected framework are determined. Article history: Received (17.07.2014); Revised (18.09.2014); Accepted (01.10.2014)